Pengaruh Lifestyle, Kelompok Referensi, Atribut Produk terhadap Keputusan Perpindahan Merek - Sri Mulyani; Yanti Murni; Maharani Putri (SAFE-Network, 2023)
Partially liftstyle has a positive and significant effect on brand switching with a calculated tvalue of 2.944 >ttable of 1.98 and a significant value of 0.004 <0.05. Partially the reference group has a positive and significant effect on brand switching with a tcount of 4.127 >ttable of 1.98 and a significant value of 0.000<0.05. Partially product attributes have no effect on brand switching with a t-value of 1.110<t-table of 1.98 and a significant value of 0.270>0.05. Simultaneously lifestyle, reference groups and product attributes have a positive and significant effect on brand switching with an Fcount of 87.221>Ftable of 2.70 and a significant value of 0.000<0.05. Then the hypothesis is accepted. The R2 test results in this study obtained an R2 value of 0.740. This shows that the influence of the independent variable on the dependent variable is 74%, while the remaining 26% is influenced by other factors not examined in this study.